1995
DOI: 10.1523/jneurosci.15-10-06779.1995
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptors in the nucleus accumbens shell control feeding behavior via the lateral hypothalamus

Abstract: The nucleus accumbens in a brain region considered to be important in the regulation of appetitive behavior and reinforcement. The accumbens receives afferent input from corticolimbic and thalamic structures, which is primarily coded by excitatory amino acids (EAAs). The present studies investigated the role of EAA input to the nucleus accumbens in feeding behavior in rats, in two recently characterized subregions of the accumbens, the "core" and "shell". In the first series of experiments, it was shown that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
241
3
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(262 citation statements)
references
References 49 publications
17
241
3
1
Order By: Relevance
“…The antiepileptic activity of ZNS may be mediated by a decreased production of GABA transporters, resulting in increased tissue and synaptic concentrations of GABA and enhanced GABA mediated neuronal inhibition (Czapinski et al, 2005). ZNS is also thought to potentially inhibit glutamate mediated neuronal excitation (Maldonado-Irizarry et al, 1995). This may explain our finding that ZNS attenuated the degree of OLZ-associated Fos-LI in the nucleus accumbens.…”
Section: Discussionmentioning
confidence: 76%
“…The antiepileptic activity of ZNS may be mediated by a decreased production of GABA transporters, resulting in increased tissue and synaptic concentrations of GABA and enhanced GABA mediated neuronal inhibition (Czapinski et al, 2005). ZNS is also thought to potentially inhibit glutamate mediated neuronal excitation (Maldonado-Irizarry et al, 1995). This may explain our finding that ZNS attenuated the degree of OLZ-associated Fos-LI in the nucleus accumbens.…”
Section: Discussionmentioning
confidence: 76%
“…A large series of studies demonstrated a role for glutamate in meal size using localized microinfusions in brain areas associated with feeding or reinforcement (e.g., Zeni et al 2000). Infusions of glutamate in the Nucleus Accumbens decreased food intake, while infusions of glutamate antagonists in the Nucleus Accumbens increased food intake by increasing meal size rodents (Maldonado-Irizarry et al 1995;Stratford et al 1998;Zeni et al 2000), and central infusions of glutamate agonists and antagonists in the pigeon produced a similar pattern of results (Da Silva et al 2006;Gillespie et al 2005). Several studies have also shown that peripheral administration of the NMDA non-competitive antagonist (+)MK-801 (dizocilpine) also increased meal size in the rat (Treece et al 2000;Jahng and Houpt 2001), perhaps due to an increase in the rate of gastric emptying (Covasa et al 2000).…”
Section: Discussionmentioning
confidence: 94%
“…Conversely, in caudal shell, agonist microinjections reveal a 'hedonic coldspot', where opioid stimulation suppresses sucrose hedonic impact (Castro and Berridge, 2014;Pecina and Berridge, 2005). By contrast to the localized hotspot for sweetness 'liking', mu-opioid stimulations increase motivation to eat much more widely and homogeneously throughout the entire NAc shell (and in related structures), measured as increases in cue-triggered 'wanting' to obtain food rewards (eg, in instrumental breakpoint and pavlovian-instrumental transfer tests), as well as in food consumption (Castro and Berridge, 2014;Covelo et al, 2014;Maldonado-Irizarry et al, 1995;Pecina and Berridge, 2005;Pecina and Berridge, 2013;Smith and Berridge, 2005;Smith et al, 2011;Zhang and Kelley, 2000).…”
Section: Introductionmentioning
confidence: 99%